There is a typo in nLab's page about fixed point combinators, the term $S (K(SII)) (S(S(KS)(S(KK)I))) (K(SII))$ is not a fixed point combinator.
Indeed, the $\lambda$-term $S (K(SII)) (S(S(KS)(S(KK)I))) (K(SII))$ (where $K$, $S$ and $I$ are interpreted by the $\lambda$-terms you wrote) $\beta$-reduces in several steps to the $\beta$-normal form $\lambda xy.xx(yy)$ (in accordance with SKI interpreter, as you correctly wrote, see below for a proof). This is in contradiction with the fact that every fixed point combinator is not $\beta$-normalizable (see below for a proof).
The source of the error in nLab's page seems to be Point 4 in the example of combinators on nLab's page about partial combinatory algebra. See here for a proper discussion.
Let us show that every fixed point combinator $P$ is not $\beta$-normalizable, that is, there is no $\beta$-normal form $N$ such that $P \to_\beta^* N$ (as usual, $\to_\beta^*$ is the reflexive-transitive closure of $\beta$-reduction step $\to_\beta$: thus, $P \to_\beta^* N$ means that $P$ $\beta$-reduces to $N$ in several $\beta$-reduction steps).
Assume, for the sake of contradiction, that $P$ is $\beta$-normalizable, that is, $P \to_\beta^* N$ for some $\beta$-normal form $N$.
It is easy to show that for every $\beta$-normal term $M$ and every variable $x$, $Mx$ is $\beta$-normalizable.
Let $N'$ be the $\beta$-normal form of $Nx$.
By definition of fixed point combinator, for every variable $x$, one has $Px =_\beta x(Px)$ ($=_\beta$ is $\beta$-equivalence, the symmetric and reflexive-transitive closure of $\to_\beta$), hence $Nx =_\beta x(Nx)$ and so $N' =_\beta xN'$. Both $N'$ and $xN'$ are $\beta$-normal, thus by confluence from $N' =_\beta xN'$ it follows that $N' = xN'$ (they are syntactically equal, up to $\alpha$-conversion), which is clearly impossible.
Let us show that $S (K(SII)) (S(S(KS)(S(KK)I))) (K(SII))$ (where $K$, $S$ and $I$ are interpreted by the $\lambda$-term you wrote) $\beta$-reduces to the $\beta$-normal form $\lambda xy.xx(yy)$.
Note that the starting term is the application of $S$ to three arguments:
first argument, $K(SII)$;
second argument, $S(S(KS)(S(KK)I))$;
third argument, $K(SII)$.
Let us see how these arguments $\beta$-reduce separately.
The first and third arguments $\beta$-reduce as follows:
\begin{align}
K(SII) &\to_\beta \lambda y.(SII) \to_\beta^* \lambda yz. Iz(Iz) \to_\beta^* \lambda yz.zz
\end{align}
Concerning the second argument, this is the application of $S$ to $S(KS)(S(KK)I)$.
Now,
\begin{align}
S(KK)I &\to_\beta^* \lambda z. KKz(Iz) \to_\beta \lambda z. KKzz \to_\beta^* \lambda z. Kz \to_\beta^* \lambda z y. z = K
\\
S(KS)(S(KK)I) &\to_\beta^* S(KS)K \to_\beta^* \lambda z. KSz(Kz) \to_\beta^* \lambda z. S(Kz) \to_\beta \lambda z. S (\lambda y.z)
\end{align}
Therefore,
\begin{align}
S\big(S(KS)(S(KK)I)\big) &\to_\beta^* S \lambda z. S (\lambda y.z) \to_\beta \lambda yz. (\lambda z'.S(\lambda y'.z'))z (yz)
\\&\to_\beta \lambda yz. S(\lambda y'.z)(yz)
\to_\beta^* \lambda yzz'.(\lambda y'.z)z' (yzz')
\\
&\to_\beta \lambda yzz'.z (yzz')
\end{align}
Putting everything together, we have
\begin{align}
S (K(SII)) (S(S(KS)(S(KK)I))) (K(SII))
&\to_\beta^* S (\lambda yz.zz) (\lambda yzz'.z (yzz')) (\lambda yz.zz)
\\
&\to_\beta^* (\lambda yz.zz) \lambda yz.zz\big((\lambda yzz'.z (yzz'))\lambda yz.zz \big)
\\
&\to_\beta (\lambda yz.zz) \lambda yz.zz\big(\lambda zz'.z ((\lambda yz.zz)zz') \big)
\\
&\to_\beta^* (\lambda yz.zz) \lambda yz.zz\big(\lambda zz'.z (z'z') \big)
\\
&\to_\beta (\lambda z.zz) \big(\lambda zz'.z (z'z') \big)
\\
&\to_\beta (\lambda zz'.z (z'z')) \lambda zz'.z (z'z')
\\
&\to_\beta \lambda z'. (\lambda zx.z (xx))(z'z')
\\
&\to_\beta \lambda z'x. (z'z')(xx)
\end{align}